Pengaruh Pemberian Susu Formula Dengan Karies Pada Anak Usia Prasekolah - Miftahul Afiat; Pariati Pariati; Hadijah Alimuddin (Barongko: Jurnal Ilmu Kesehatan, 2022)
Background: Formula milk is milk produced by the industry for the purpose of proper nutritional intake and can be accepted by the child's body system. Dental caries is an infectious disease that can damage the hard tissue structure of the teeth, which includes enamel, dentine and cementum, caused by the activity of microorganisms in fermenting carbohydrates. Research Objectives: To determine the effect of formula feeding on caries in preschool-aged children. Research Methods: Literature study, where the literature study method is one of the techniques for listing theoretical references come from textbooks, journals, scientific articles, literature review which contains the effect of formula feeding on caries in preschool-aged children. Conclution: Consumption of formula milk has an effect on dental caries in preschool children. Carbohydrate content such as sucrose and lactose can cause dental caries and if you consume formula milk too often, the severity of dental caries will be higher.